An investigation of unemployment at Tshiheni village : Limpopo Province - Nemalili, Nkhumeleni Patricia (My University, 2006)
The main purpose of the study was to explore the causes and effects of unemployment and the impact this has on development. The study was significant as it was assisting in identifying the unemployed in Tshiheni village. Furthermore the study highlighted various factors that conspires development at the village i.e. the causes of unemployment. The study also revealed the psychological, health and socio-economic challenges faced by the unemployed at the village. It further communicated possible strategies in which the un-employed can make a living. The study is qualitative in nature and a thirty percent systematic random sampling was drawn from the population. An interview schedule was used to collect data from the seventy respondents and it is included here as appendix A. The findings of the research were that the majority of the unemployed were aged between twenty-one and thirty years, females being the most vulnerable. Unemployment was mainly caused by non-availability of jobs, followed by retrenchments and then lack of skills. Majority of respondents reported viewing themselves negatively. Half of the respondents believe that abusing drugs would help them deal with the situation. Unemployment has a negative effect on social relationships. Majority of the unemployed are not self-employed, but rely on families and child grants for support.
Thesis (M.Dev.) --University of Limpopo, 2006
Keywords: Unemployment; Unemployment -- South Africa -- Limpopo --Psychological aspects